Hands-on MQTT programming with Python work with the lightweight IoT protocol in Python - Hillar, Gastón C. (Packt Publishing, 2018)
Annotation
Online resource; title from title page (Safari, viewed June 29, 2018)
Keywords: Telecommunication -- Message processing; Business enterprises -- Computer networks; Internet of things; Python (Computer program language); Télécommunications; Traitement de messages; Entreprises; Réseaux d'ordinateurs; Internet des objets; Python (Langage de programmation); Business enterprises; Computer networks; Telecommunication; Message processing